Conductive polymer / S-CN composite material with pi-pi conjugated structure as well as preparation method and application of conductive polymer / S-CN composite material
By using conductive polymer/S-CN composites with π-π conjugated structures, the problem of limited application of photocatalytic technology in high-salt wastewater is solved, and efficient removal of tetracycline is achieved. The method is simple, low-cost and stable composite material.
Patent Information
- Application Number
- CN202411880324.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The existing photocatalytic technology is limited in the application of high-salt wastewater, especially in the treatment of high-salt-containing pharmaceutical wastewater, which lacks efficient catalysts to effectively degrade contaminants such as tetracycline.
The conductive polymer/S-CN composite material with a π-π conjugated structure is used to prepare the composite material through ultrasonic dispersion and acid regulation, and is applied to high-salt and non-high-salt wastewater under photocatalytic conditions to achieve the removal of tetracycline.
This method improves photocatalytic performance and realizes effective removal of tetracycline in high-salt and non-salt water bodies. It has a simple preparation method, low cost and good stability of composite materials.
Smart Images

Figure CN119708767A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and relates to a water treatment material, in particular to a conductive polymer / S-CN composite material with a π-π conjugated structure, a preparation method thereof, and application of the composite material in degrading tetracycline wastewater in high-salt and non-high-salt systems. Background Art
[0002] In order to achieve the goal of zero discharge, it is urgent to develop advanced high-salinity wastewater (such as landfill leachate, pharmaceutical wastewater, chemical dye wastewater) treatment technology. - ) is toxic to microorganisms and may cause excessive energy consumption and equipment corrosion, affecting treatment efficiency.
[0003] Advanced oxidation processes (AOP) can generate highly reactive free radicals such as sulfate (SO4 - ·), hydroxyl radical (·OH) and hydrogen peroxide radical (O2 - ·) and is widely used in the sewage treatment industry. Photocatalytic technology has been concerned and studied by humans for its green and renewable characteristics. However, the application of photocatalysis in high-salinity wastewater is limited. This is mainly because salt ions, especially anions (Cl - , SO4 2- The removal of pollutants may be significantly affected by blocking the active sites on the surface of the photocatalyst, scavenging photoactive substances (holes and ·OH), complexing with target pollutants, competing for photon absorption, and acting as a recombination promoter. At present, chloride ions with high ionic strength are commonly found in industrial wastewater, seawater, and marine aquaculture wastewater. So far, there is still no efficient catalyst for the treatment of pollutants in high-salt wastewater using photocatalytic technology.
[0004] Graphitic carbon nitride (g-CN) has attracted much attention in the field of photocatalysis due to its stable, economical and easy-to-synthesize two-dimensional structure. Although graphitic carbon nitride has limitations in light absorption and charge carrier transport, its photocatalytic efficiency can be improved by strategies such as doping and forming heterojunctions with other semiconductors. Polythiophene (PTH) is an organic photosensitizer with a large π-conjugated skeleton and delocalized electronic structure, so it can be used for photocatalytic hydrogen production and pollutant degradation. However, there are relatively few studies on its application in high-salinity wastewater, especially pharmaceutical wastewater. In the pharmaceutical industry, tetracycline (TC) is the second largest antibiotic produced worldwide. Pharmaceutical wastewater contains a large amount of residual tetracycline, which is characterized by high salt content and poor biodegradability.
[0005] The Chinese invention patent application with publication number CN115106127A discloses a method for preparing a ternary MOF-derived zinc-titanium nanocomposite material that can photocatalytically degrade tetracycline. The conventional method of the invention prepares MH-2-MIL-125, then uses dimethimidazole and Co(NO3)2·6H2O as raw materials to generate ZIF-67 on the outer surface of NH-2-MIL-125 to form a binary MOF structure of NH-2-MIL-125@ZIF-67, and then uses 2-methylimidazole Zn(NO3)2·6H2O as a raw material to generate ZIF-8 on the surface of NH-2-MIL-125@ZIF-67 to form a ternary MOF structure of NH-2-MIL-125@ZIF-67@ZIF-8, and finally calcines it to obtain a ternary MOF-derived zinc-titanium composite nanomaterial for degrading tetracycline. However, the catalyst synthesis process is complicated and does not take into account the impact of the high salt problem in actual tetracycline wastewater.
[0006] The Chinese invention patent application with publication number CN117181248A discloses a bismuth-complex oxychloride / bismuth tungstate heterojunction photocatalytic material and its preparation method and application in removing tetracycline from water. 12 O 17 The bismuth oxychloride / bismuth tungstate heterojunction photocatalytic material is mixed with water containing tetracycline under visible light irradiation to carry out photocatalytic reaction. The invention tests the degradation of tetracycline in daily water, and does not consider the effect of high salinity on photocatalytic performance in high-concentration pharmaceutical wastewater.
[0007] The Chinese invention patent application with publication number CN118594529A discloses a method for preparing an In2O3 / Mn2O3 photocatalytic composite material and its application in synergistic PMS degradation of tetracycline wastewater. The invention provides a method for preparing an In2O3 / Mn2O3 photocatalytic composite material, firstly preparing a precursor MIL-68 (In) by a hydrothermal method; further combining it with manganese acetate to form a heterojunction to obtain an In2O3 / Mn2O3 photocatalytic composite material; finally adding PMS to activate and construct an In2O3 / Mn2O3-PMS photocatalytic system to degrade tetracycline. However, the invention requires a synergistic PMS system, which increases the cost and energy consumption of tetracycline degradation.
[0008] The Chinese invention patent application with publication number CN118374005A discloses a zinc coordination polymer for photocatalytic degradation of antibiotics and a preparation method thereof. The chemical formula of the zinc coordination polymer is: {[Zn(ipa)(Hpap)]·2H2O}n, where n is an infinitely repeated structural unit. The invention proposes that the zinc coordination polymer has excellent water stability and can effectively photocatalytically degrade tetracycline hydrochloride. However, the catalyst preparation of the invention is complicated, contains metal materials, and the cycle experiment is only three times, which increases the risk of catalyst instability.
[0009] The Chinese invention patent application with publication number CN116970108A discloses a method for synthesizing protonated carbon nitride nanosheets / conductive polymer composite materials by low-temperature photopolymerization under atmosphere control. The method first uses a hydrothermal reaction to obtain protonated g-C3N4 nanosheets; then uses a sodium dodecyl sulfate solution to treat the protonated g-C3N4 nanosheets; and finally uses a light source to obtain a protonated carbon nitride nanosheet / conductive polymer composite material under low-temperature ice-salt bath conditions of -20 to 5°C. The preparation method of the composite material is complicated, and the material has not been studied and applied in wastewater treatment. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention is based on photocatalytic technology and aims to provide a conductive polymer / S-CN composite material with a π-π conjugated structure and a preparation method, and its application in degrading tetracycline wastewater in high-salt and non-high-salt systems.
[0011] To achieve the above object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a method for preparing a conductive polymer / S-CN composite material having a π-π conjugated structure, comprising the following steps:
[0013] Step 1, dispersing the conductive polymer and S-CN in water respectively, and obtaining a polymer suspension and an S-CN suspension respectively after ultrasonic treatment;
[0014] Step 2: adjusting the pH of the S-CN suspension to acidic, and then gradually introducing the polymer suspension into the S-CN suspension under continuous stirring; ultrasonic stirring;
[0015] Step 3: Wash the material obtained in step 2 with ethanol and pure water until it is neutral, and dry it to obtain a conductive polymer / S-CN composite material.
[0016] Furthermore, in step 1, the S-CN is a two-dimensional nanosheet, and the preparation method is: dissolving urea and tannic acid (TA) in methanol, and stirring to dryness at 80° C.; calcining the obtained solid to obtain the S-CN.
[0017] Furthermore, in the preparation method of S-CN, the calcination temperature is 500-600° C., and the calcination time is 3-5 hours, preferably calcined at 550° C. for 4 hours.
[0018] Furthermore, in step 1, the conductive polymer is one or more of polythiophene, polyaniline, and polypyrrole.
[0019] Furthermore, the preparation method of the polythiophene is: dissolving thiophene in chloroform, adding anhydrous ferric chloride, and vigorously stirring; filtering, washing, and drying the obtained mixture to obtain the polythiophene; the dosage ratio of thiophene, chloroform, and anhydrous ferric chloride is 0.1-0.2 ml: 20-30 ml: 1-1.5 g, preferably 0.179 ml: 25 ml: 1.3 g;
[0020] The preparation method of the polyaniline is as follows: dissolving aniline and ammonium persulfate in 0.5M sulfuric acid and cooling in an ice bath for 8 hours; washing and drying the obtained solution to obtain the polyaniline; the usage ratio of aniline to ammonium persulfate is 0.1-0.3ml:0.1-0.3g, preferably 0.2277ml:0.206g.
[0021] The preparation method of polypyrrole comprises: dissolving sodium dodecyl sulfate in water and dispersing by ultrasonication; adding pyrrole dropwise under ice bath conditions, then adding anhydrous ferric chloride and continuing stirring; washing and drying the obtained mixture to obtain polypyrrole; the dosage ratio of sodium dodecyl sulfate, pyrrole and anhydrous ferric chloride is 0.01-0.03g: 3-8μL: 0.02-0.04g, preferably 0.02g: 5μL: 0.03g.
[0022] Furthermore, in step 2, the mass ratio of the conductive polymer to S-CN is 1-10:100.
[0023] In a second aspect, the present invention also provides a conductive polymer / S-CN composite material having a π-π conjugated structure obtained by the above-mentioned preparation method.
[0024] In a third aspect, the present invention also provides the use of the above-mentioned conductive polymer / S-CN composite material with a π-π conjugated structure in photocatalytic removal of tetracycline in high-salinity wastewater.
[0025] Furthermore, the application method is: adding the conductive polymer / S-CN composite material to wastewater containing tetracycline, stirring in the dark to perform adsorption reaction, and after reaching adsorption-desorption equilibrium, turning on a light source of λ>420nm to perform photocatalytic reaction.
[0026] Furthermore, the ratio of the amount of the conductive polymer / S-CN composite material to the concentration of tetracycline in the wastewater is 10-20 mg: 10 mg / L.
[0027] The present invention is based on the structural advantages and excellent photosensitivity of sulfur-doped carbon nitride (S-CN) and polymers, and constructs a conductive polymer / S-CN composite material by electrostatic self-assembly. Sulfur doping is used to introduce an intermediate band gap into the catalyst, thereby enhancing light absorption; the polymer broadens the light absorption spectrum of the composite material and promotes the transfer of electrons. The present invention improves the photocatalytic performance and realizes the effective removal of pollutants in non-high-salt / high-salt water bodies.
[0028] The beneficial effects of the present invention are:
[0029] 1. The preparation method of the conductive polymer / S-CN composite material of the present invention is simple and the production cost is relatively low. The S-CN prepared by doping S has a good light absorption range, which further promotes the excitation of photogenerated electrons of the conductive polymer / S-CN; the special photosensitivity of the conductive polymer improves the utilization efficiency of the conductive polymer / S-CN for light, changes the form of electronic transition, and thus produces more active species to participate in the degradation process of tetracycline in high-salt and non-high-salt water bodies, thereby showing an excellent removal effect.
[0030] Second, the present invention is used to remove tetracycline from non-high-salt / high-salt wastewater, with mild reaction conditions, simple and easy operation, rapid and effective. By adjusting the dosage of the composite material and the reaction time, the performance and efficiency of the composite material in removing pollutants can be controlled. At the same time, the composite material treated by this method is easy to recycle and has good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a diagram of the preparation process of the conductive polymer / S-CN composite material of the present invention;
[0032] Figure 2 are scanning electron microscope images of polythiophene (a) and polythiophene / S-CN (b) prepared in Example 1;
[0033] Figure 3 are UV-visible diffuse reflectance spectra of g-CN, S-CN prepared in Example 1, and PTh / S-CN prepared in Examples 1 to 4;
[0034] Figure 4 are electrochemical impedance spectra of g-CN, S-CN prepared in Example 1, and PTh / S-CN prepared in Examples 1 to 4;
[0035] Figure 5 This is a graph showing the effects of conductive polymer / S-CN and other control groups on the degradation of tetracycline in non-high-salinity (a) / high-salinity (b) water bodies;
[0036] Figure 6 This is the cycling performance diagram of conductive polymer / S-CN under photocatalytic conditions. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific embodiments.
[0038] Example 1
[0039] This embodiment provides a conductive polymer / S-CN composite material with a π-π conjugated structure, and the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0040] Step 1: Ultrasonic dispersion of 5 mg polythiophene (PTh) in 50 ml pure water for 2 h to obtain a polythiophene suspension. Ultrasonic dispersion of 100 mg S-CN in 100 ml pure water for 2 h to obtain a S-CN suspension.
[0041] The preparation method of polythiophene is as follows: 0.179 ml of thiophene is dissolved in 25 ml of chloroform, and the mixture is stirred for 20 minutes. Subsequently, 1.3 g of anhydrous ferric chloride is added to the mixture, and the mixture is stirred vigorously for 2 hours. The resulting mixture is filtered, washed with methanol and dilute hydrochloric acid, and then vacuum dried at 60°C to obtain deep red polythiophene.
[0042] The preparation method of S-CN is as follows: 6 g of urea and 20 mg of tannic acid (TA) are directly added to a beaker containing methanol, and then stirred at 80°C to evaporate the solvent. The resulting solid is transferred to a crucible, which is then sealed with aluminum foil and placed in a muffle furnace. The temperature is raised to 550°C and calcined for 4 hours to obtain S-CN.
[0043] Step 2: Adjust the pH value of the S-CN suspension to 4, and then gradually introduce the polythiophene suspension into the S-CN suspension under continuous stirring. Stir for 6 hours.
[0044] Step 3: Wash the mixture with ethanol and pure water until it reaches neutrality, and then dry it in vacuum at 60° C. to obtain PTh / S-CN, which is recorded as 5% PTh / S-CN based on the mass ratio of PTh to S-CN.
[0045] Figure 2 a in Figure 1 is a scanning electron microscope image of PTh, and b is a scanning electron microscope image of PTh / S-CN. Figure 2 It can be seen that the conductive polymer PTh shows a stacked rod-like structure, and the layered film structure of S-CN in PTh / S-CN is cross-linked with the rod-like conductive polymer.
[0046] The PTh in this embodiment can also be replaced by polyaniline (PANI) or polypyrrole (PPy), and the obtained composite materials are PANI / S-CN and PPy / S-CN.
[0047] The preparation method of polyaniline is as follows: 0.2277 ml of aniline and 0.206 g of ammonium persulfate are dissolved in 100 ml of 0.5 M sulfuric acid, and then cooled in an ice bath for 8 hours. The resulting solution is washed alternately with pure water and ethanol until neutral, and then vacuum dried at 60°C to obtain dark green polyaniline.
[0048] The preparation method of polypyrrole is as follows: 0.02g sodium dodecyl sulfate is dissolved in 70ml pure water, and then dispersed by ultrasonic wave for 30min. Under ice bath condition, 5μL pyrrole is added dropwise and stirred for 30min, and then 0.03g anhydrous ferric chloride is added and stirred for 1h. Then the resulting mixture is left to stand for 1h, washed alternately with pure water and ethanol until neutral, and dried in vacuum at 60℃ to obtain dark brown polypyrrole.
[0049] Example 2
[0050] This embodiment provides a conductive polymer / S-CN composite material with a π-π conjugated structure, and the preparation method includes the following steps:
[0051] Step 1: Ultrasonic dispersion of 1 mg polythiophene (PTh) in 50 ml pure water for 2 h to obtain a polythiophene suspension. Ultrasonic dispersion of 100 mg S-CN in 100 ml pure water for 2 h to obtain a S-CN suspension. The preparation methods of polythiophene and S-CN are the same as those in Example 1.
[0052] Step 2: Adjust the pH value of the S-CN suspension to 4, and then gradually introduce the polythiophene suspension into the S-CN suspension under continuous stirring. Stir for 6 hours.
[0053] Step 3: Wash the mixture with ethanol and pure water until it reaches neutrality, and then dry it in vacuum at 60° C. to obtain PTh / S-CN, which is recorded as 1% PTh / S-CN based on the mass ratio of PTh to S-CN.
[0054] Example 3
[0055] This embodiment provides a conductive polymer / S-CN composite material with a π-π conjugated structure, and the preparation method includes the following steps:
[0056] Step 1: Ultrasonic dispersion of 3 mg polythiophene (PTh) in 50 ml pure water for 2 h to obtain a polythiophene suspension. Ultrasonic dispersion of 100 mg S-CN in 100 ml pure water for 2 h to obtain a S-CN suspension. The preparation methods of polythiophene and S-CN are the same as those in Example 1.
[0057] Step 2: Adjust the pH value of the S-CN suspension to 4, and then gradually introduce the polythiophene suspension into the S-CN suspension under continuous stirring. Stir for 6 hours.
[0058] Step 3: Wash the mixture with ethanol and pure water until it reaches neutrality, and then dry it in vacuum at 60° C. to obtain PTh / S-CN, which is recorded as 3% PTh / S-CN based on the mass ratio of PTh to S-CN.
[0059] Example 4
[0060] This embodiment provides a conductive polymer / S-CN composite material with a π-π conjugated structure, and the preparation method includes the following steps:
[0061] Step 1: Ultrasonic dispersion of 10 mg polythiophene (PTh) in 50 ml pure water for 2 h to obtain a polythiophene suspension. Ultrasonic dispersion of 100 mg S-CN in 100 ml pure water for 2 h to obtain a S-CN suspension. The preparation methods of polythiophene and S-CN are the same as those in Example 1.
[0062] Step 2: Adjust the pH value of the S-CN suspension to 4, and then gradually introduce the polythiophene suspension into the S-CN suspension under continuous stirring. Stir for 6 hours.
[0063] Step 3: Wash the mixture with ethanol and pure water until it reaches neutrality, and then dry it in vacuum at 60° C. to obtain PTh / S-CN, which is recorded as 10% PTh / S-CN according to the mass ratio of PTh to S-CN.
[0064] The UV-visible diffuse reflectance spectra of g-CN, S-CN prepared in Example 1, and PTh / S-CN prepared in Examples 1 to 4 were measured. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that a red shift is observed in the light absorption edge of PTh / S-CN. Compared with g-CN, the introduction of S-CN and PTh broadens the light absorption range of the composite material.
[0065] The electrochemical impedance spectroscopy of g-CN, S-CN prepared in Example 1, and PTh / S-CN prepared in Examples 1 to 4 was tested. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that compared with S-CN, the electrochemical impedance spectroscopy arc radius of PTh / S-CN is smaller, which indicates that the conductive polymer / S-CN has good electron conduction ability and can improve the interfacial charge transfer performance of the composite material, thereby improving its photocatalytic performance.
[0066] Example 5
[0067] This embodiment provides the application of the above-mentioned conductive polymer / S-CN composite material with a π-π conjugated structure in photocatalytic removal of tetracycline in high-salinity wastewater.
[0068] Application experiment 1:
[0069] Experimental group: simulated wastewater (high salt) of 10.00mg / l tetracycline and 0.5M NaCl and simulated wastewater (non-high salt) of 10.00mg / l tetracycline were prepared with deionized water. 50ml of simulated wastewater was added to a quartz tube with a cooling jacket. Then 20mg of the conductive polymer / S-CN composite material prepared in Example 1 was added, and a magnetic stirrer was added, and the mixed system was placed in a photocatalytic reaction device. The condensation circulating water was turned on, and the adsorption reaction was carried out at 350rpm under light-proof magnetic stirring. After stirring for 1h to reach adsorption-desorption equilibrium, the xenon light source was turned on for photocatalytic reaction, and magnetic stirring was continued at 300rmp. Samples were taken regularly, and 1ml of the reaction solution was drawn each time, filtered by a filter membrane, and placed in a vial. Finally, the tetracycline concentration was measured using an ultraviolet spectrophotometer.
[0070] Control group 1: The S-CN prepared in Example 1 was used as a catalyst to perform a photocatalytic degradation experiment on tetracycline in non-high-salt / high-salt simulated wastewater. The experimental process was the same as that of the above experimental group.
[0071] Control group 2: g-CN was used as a catalyst to conduct a photocatalytic degradation experiment on tetracycline in non-high-salt / high-salt simulated wastewater. The experimental process was the same as that of the above experimental group.
[0072] Control group 3: No catalyst was added, and the tetracycline pollutant was directly photodegraded using visible light. The experimental process was the same as that of the above experimental group.
[0073] The removal effect of each group is as follows Figure 5 As shown. Figure 5 It can be seen that under visible light, without adding a catalyst, tetracycline is almost not degraded within 2 hours. The removal rate of tetracycline in non-high salt / high salt water by conductive polymer / S-CN within 2 hours is about 80% and 70%, respectively, which effectively improves the removal effect of tetracycline in different water bodies.
[0074] Application experiment 2:
[0075] The composite materials after the experimental group of application experiment 1 were collected, filtered, washed, and dried for the next round of experiments. The experimental process of each round was the same as that of the experimental group in application experiment 1 to evaluate the stability of the conductive polymer / S-CN composite materials.
[0076] Removal effect Figure 6 As shown. Figure 6 It can be seen that after five consecutive uses, the removal rate of tetracycline by the composite material can still be maintained above 70%, which shows that the conductive polymer / S-CN composite material has good stability and reusability, and proves that the conductive polymer / S-CN composite material prepared by electrostatic self-assembly method is a method that can efficiently remove tetracycline in non-high salt / high salt water bodies.
[0077] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.
[0078] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a conductive polymer / S-CN composite material having a π-π conjugated structure, characterized in that: The following steps are involved: Step 1, dispersing the conductive polymer and S-CN in water respectively, and obtaining a polymer suspension and an S-CN suspension respectively after ultrasonic treatment; Step 2: adjusting the pH of the S-CN suspension to acidic, and then gradually introducing the polymer suspension into the S-CN suspension under continuous stirring; Ultrasonic stirring; Step 3: Wash and dry the material obtained in step 2 to obtain a conductive polymer / S-CN composite material.
2. The method for preparing the conductive polymer / S-CN composite material having a π-π conjugated structure according to claim 1, characterized in that: In step 1, the preparation method of the S-CN is: dissolving urea and tannic acid in methanol and stirring to dryness; calcining the obtained solid to obtain the S-CN.
3. The method for preparing the conductive polymer / S-CN composite material having a π-π conjugated structure according to claim 2, characterized in that: In the preparation method of S-CN, the mass ratio of urea to tannic acid is 200-400:1; The calcination temperature is 500-600°C, and the calcination time is 3-5h.
4. The method for preparing the conductive polymer / S-CN composite material having a π-π conjugated structure according to claim 1, characterized in that: In step 1, the conductive polymer is one or more of polythiophene, polyaniline, and polypyrrole.
5. The method for preparing the conductive polymer / S-CN composite material having a π-π conjugated structure according to claim 4, characterized in that: The preparation method of the polythiophene is as follows: dissolving thiophene in chloroform, adding anhydrous ferric chloride, and vigorously stirring; filtering, washing, and drying the obtained mixture to obtain the polythiophene; The preparation method of the polyaniline is as follows: dissolving aniline and ammonium persulfate in sulfuric acid, and cooling in an ice bath (8 hours); washing and drying the obtained solution to obtain the polyaniline; The preparation method of polypyrrole is as follows: dissolving sodium dodecyl sulfate in water and dispersing by ultrasonication; In an ice bath, pyrrole is added dropwise, and then anhydrous ferric chloride is added and stirred continuously; the obtained mixture is washed and dried to obtain polypyrrole.
6. The method for preparing the conductive polymer / S-CN composite material having a π-π conjugated structure according to claim 1, characterized in that: In step 2, the mass ratio of the conductive polymer to S-CN is 1-10:
100.
7. The conductive polymer / S-CN composite material having a π-π conjugated structure obtained by the preparation method according to claim 1.
8. Use of the conductive polymer / S-CN composite material with a π-π conjugated structure as claimed in claim 7 in photocatalytic removal of tetracycline in high-salinity wastewater.
9. Use of the conductive polymer / S-CN composite material with a π-π conjugated structure according to claim 8 in photocatalytic removal of tetracycline in wastewater, characterized in that: The application method is as follows: adding the conductive polymer / S-CN composite material to wastewater containing tetracycline, stirring in the dark to carry out adsorption reaction, and after reaching adsorption-desorption equilibrium, turning on the light source to carry out photocatalytic reaction.
10. The method for preparing the conductive polymer / S-CN composite material having a π-π conjugated structure according to claim 9, characterized in that: The ratio of the amount of the conductive polymer / S-CN composite material to the concentration of tetracycline in the wastewater is 10-20 mg: 10 mg / L.
Citation Information
Patent Citations
Preparation method of ternary MOF (Metal Organic Framework) derived zinc-titanium nano composite material capable of photocatalytically degrading tetracycline
CN115106127A
Method for synthesizing protonated carbon nitride nanosheet / conducting polymer composite material through low-temperature photopolymerization induction under atmosphere regulation and control
CN116970108A
Compound bismuth type bismuth oxychloride / bismuth tungstate heterojunction photocatalytic material, preparation method thereof and application of photocatalytic material in removal of tetracycline in water body
CN117181248A
Zinc coordination polymer for photocatalytic degradation of antibiotics and preparation method thereof
CN118374005A
Preparation method of In2O3 / Mn2O3 photocatalytic composite material and application of In2O3 / Mn2O3 photocatalytic composite material in degradation of tetracycline wastewater in cooperation with PMS
CN118594529A